1998
DOI: 10.3109/08860229809045127
|View full text |Cite
|
Sign up to set email alerts
|

Source of Reactive Oxygen Species in Anti-Thy1 Nephritis

Abstract: In proliferative glomerulonephritis, both macrophages and mesangial cells generate reactive oxygen species (ROS), contributing to the development of glomerular injury. We have attempted to determine which cell produces ROS during anti-Thy1 nephritis (ATN) in rats. The generation of ROS was studied using luminol amplified chemiluminescence (GCL) on isolated glomeruli. Immunohistochemical studies used avidin-biotin complex (ABC) to label macrophages and mesangial cells. Immediately after ATN induction, mesangiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Nevertheless, macrophages that infiltrated into the interstitium can release ROS (26). It is reported that ROS generated by the infiltrated macrophages contribute in the development of renal disease (27). Thus, DPPD may have scavenged macrophage-derived ROS and attenuated ROS-mediated fibrogenetic process, a possibility that must be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, macrophages that infiltrated into the interstitium can release ROS (26). It is reported that ROS generated by the infiltrated macrophages contribute in the development of renal disease (27). Thus, DPPD may have scavenged macrophage-derived ROS and attenuated ROS-mediated fibrogenetic process, a possibility that must be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) released from inflammatory cells play a critical role in the pathogenesis of thy-1 nephritis [26]. A previous study showed that a scavenger for ROS suppressed urinary protein and the proliferation of mesangial cells in thy-1 nephritis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) released from inflammatory cells play a critical role in the pathogenesis of Thy-1 nephritis [24]. A previous study showed that a scavenger for ROS suppressed urinary protein and the proliferation of mesangial cell in Thy-1 nephritis [25].…”
Section: Discussionmentioning
confidence: 99%